Musculoskeletal adverse events reported post-hepatitis B vaccination in the vaccine adverse event reporting system - Sun, Yiqing; Zhu, Bukun; Li, Xiang; Luo, Zhanyang; Bian, Weiguo (Frontiers in Public Health, 2025)
IntroductionHepatitis B virus (HBV) is a major cause of chronic liver disease. While the hepatitis B vaccine has been proven effective in preventing HBV infection, concerns regarding Events Supposedly Attributable to Vaccination or Immunization (ESAVI) persist. This study aims to utilize the Vaccine Adverse Event Reporting System (VAERS) database to explore potential associations between the hepatitis B vaccine and musculoskeletal system AEs, providing a scientific basis for vaccine safety evaluations.MethodsThis study analyzed VAERS data from 1990 to 2024, focusing on 76,887 reports associated with hepatitis B vaccines. Disproportionality analysis methods, such as the Proportional Reporting Ratio (PRR) and Reporting Odds Ratio (ROR), were applied to identify the distribution and signal strength of musculoskeletal-related AEs. Furthermore, multivariable logistic regression analysis was conducted to explore association between patients with HBV vaccine and death.ResultsMusculoskeletal system ESAVIs constituted a significant portion of all reports, including tendon fibrosis (ROR = 251.82), myofascitis (ROR = 107.51), fasciitis (ROR = 71.52), and osteoarthritis (ROR = 7.56). Tendon fibrosis demonstrated the strongest association, potentially linked to chronic inflammatory responses and abnormal tissue repair induced by aluminum adjuvants. Most AEs occurred within 30 days post-vaccination, though some, such as myofascitis, had a longer mean onset time (1,671 days), reflecting the slow-release properties of aluminum adjuvants. In multivariable logistic regression analysis, we concluded that male and combination vaccine treatment were risk factors while age from18-64 years was a protective factors of death.ConclusionThis study identifies potential associations between hepatitis B vaccination and musculoskeletal system AEs, emphasizing the need for thorough pre-vaccination assessments and post-vaccination monitoring for high-risk individuals.